﻿Fabrication of blended chitosan nanofibers by the free surface wire electrospinning - Nawzat D., AlJbour; Mohammad Dalour, Hossen Beg; Jolius, Gimbun; Mior Ahmad Khushairi, Mohd Zahari (Pensoft, 2023)
Nanofibers are fibers with diameters in the nanometer range. They are characterized by their high surface area to volume ratio, flexible surface functionalities, and superior mechanical properties. Chitosan is a polycationic polymer which is abundant in nature. Chitosan nanofibers have been widely explored for different potential applications such as wound dressing, tissue engineering, and drug delivery systems. It is difficult to directly spin pure chitosan, due to its high molecular weight, low solubility, and high viscosity. To produce nanofibers, chitosan is commonly blended with other polymers that possess fiber forming capabilities such as polyvinyl alcohol, polycaprolactone, and Polylactic acid. In this study chitosan oligomers of an average molecular weight 15 kDa was blended with the three copolymers at different weight ratios. The fibers were prepared by the free surface wire electrospinning process, and the formed Chitosan nanofibers were characterized by Scanning Electron Microscopy (SEM). SEM results showed that blending chitosan with PLA enhances its spinnability and facilitates uniform and smooth morphology. Blending chitosan with PLA produced nanofibers with better quality, compared to PVA, and PCL